Profesionalisme Guru Pendidikan Agama Kristen Di Tengah Arus Globalisasi - Halomoan, Samuelson; Napitupulu, Dody Kasih; Eunike, Sumingse; Gea, Yuniman; Sitorus, Hisardo (Institut Agama Kristen Negeri Tarutung, 2025)
Globalization has a significant impact on Christian religious education, particularly in terms of value changes, social media ethics, and religious pluralism. Christian Religious Education teachers face the challenge of maintaining religious values amid the rapid flow of information and technological advancements. This study aims to identify the challenges faced by teachers and propose efforts to enhance their professionalism. Using a qualitative method through literature study, this research analyzes relevant sources to understand the impact of globalization on Christian religious teaching. The results indicate that globalization causes a crisis of values and changes in ethics, but also opens opportunities for teachers to integrate technology wisely and collaborate with parents and the community. Competency enhancement through training and the development of digital skills is crucial for teachers to teach Christian values that are relevant to the changing times. This study is expected to contribute to the development of adaptive and inclusive Christian religious education.